Photochemical Oxidation of Oil Reduced the Effectiveness of Aerial Dispersants Applied in Response to the Deepwater Horizon Spill - Ward, Collin P; Armstrong, Cassia J; Conmy, Robyn N; French-McCay, Deborah P; Reddy, Christopher M (Environmental science & technology letters, 2018)
Chemical dispersants are one of many tools used to mitigate the overall environmental impact of oil spills. In principle, dispersants break up floating oil into small droplets that disperse into the water column where they are subject to multiple fate and transport processes. The effectiveness of dispersants typically decreases as oil weathers in the environment. This decrease in effectiveness is often attributed to evaporation and emulsification, with the contribution of photochemical weathering assumed to be negligible. Here, we aim to test this assumption using Macondo well oil released during the Deepwater Horizon spill as a case study. Our results indicate that the effects of photochemical weathering on Deepwater Horizon oil properties and dispersant effectiveness can greatly outweigh the effects of evaporative weathering. The decrease in dispersant effectiveness after light exposure was principally driven by the decreased solubility of photo-oxidized crude oil residues in the solvent system that comprises COREXIT EC9500A. Kinetic modeling combined with geospatial analysis demonstrated that a considerable fraction of aerial applications targeting Deepwater Horizon surface oil had low dispersant effectiveness. Collectively, the results of this study challenge the paradigm that photochemical weathering has a negligible impact on the effectiveness of oil spill response and provide critical insights into the “window of opportunity” to apply chemical dispersants in response to oil spills in sunlit waters.